EFEKTIVITAS PEGUNAAN LABORATORIUM IPA DALAM PEMBELAJARAN DI MTsN 1 BANYUWANGI - Syaiful Rijal (Program Studi Pendidikan Biologi, 2021)
Abstract: This study aims to determine the effectiveness of the use of the science laboratory in learning process at MTsN 1 Banyuwangi including the completeness of facilities and infrastructure, administration of the science laboratory and the use of the science laboratory. This type of research is a qualitative research using interview data collection methods, observation and documentation. The data analysis technique in this study is a descriptive data analysis technique. Based on the findings of the analysis that the facilities and infrastructure (tools, goods and materials) of the science laboratory, the conditions of the laboratory room and the layout of the storage for tools, goods and materials, the school has carried out maintenance, provided tools and materials for practicum and increased laboratory usability is 100% and in the complete category. The school's Science Laboratory Administration has provided administration, for example borrowing goods, journals, activity schedules, labels and inventory books are in the complete category. The use of science laboratories has carried out practicum once a week for each class that is categorized as effective.